2019
DOI: 10.1101/806232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluorescence photography of patterns and waves of bacterial adaptation at high antibiotic doses

Abstract: Fisher suggested advantageous genes would spread through populations as a wave so we sought genetic waves in evolving populations, as follows. By fusing a fluorescent marker to a drug efflux protein (AcrB) whose expression provides Escherichia coli with resistance to some antibiotics, we quantified the evolution and spread of drug-resistant E. coli through spacetime using image analysis and quantitative PCR. As is done in hospitals routinely, we exposed the bacterium to a gradient of antibiotic in a 'disk diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…13 Heterogeneous drug susceptibility within a population can also arise from the stochastic expression of genes encoding intrinsic antibiotic-resistance mechanisms, notably efflux pumps. 14,15 Rapid adaptation to antibiotics can also be achieved through genomic duplications that increase the dosage of known drug-resistance genes, 8,16,17 for instance through amplification of efflux pump operons 18,19 or genes encoding drug-modifying enzymes. 20,21 Laboratory studies have shown that genomic amplifications scale up with the strength of the selective pressure, 16 and are unstable in the absence of selection due to the fitness burden associated with the duplication of large chromosome regions.…”
Section: Introductionmentioning
confidence: 99%
“…13 Heterogeneous drug susceptibility within a population can also arise from the stochastic expression of genes encoding intrinsic antibiotic-resistance mechanisms, notably efflux pumps. 14,15 Rapid adaptation to antibiotics can also be achieved through genomic duplications that increase the dosage of known drug-resistance genes, 8,16,17 for instance through amplification of efflux pump operons 18,19 or genes encoding drug-modifying enzymes. 20,21 Laboratory studies have shown that genomic amplifications scale up with the strength of the selective pressure, 16 and are unstable in the absence of selection due to the fitness burden associated with the duplication of large chromosome regions.…”
Section: Introductionmentioning
confidence: 99%
“…Lab scanners are widely used for high throughput colony counting and growth analysis ( Hartman and Tippery, 2004 ; Michel et al, 2008 ; Clarke et al, 2010 ; Levin-Reisman et al, 2014 ), although the mode of image capture through the bottom of the agar plate limits the resolution of morphological features. Other apparatuses have been custom-made for automated colony counting ( Clarke et al, 2010 ; Brugger et al, 2012 ), imaging colonies in soft agar ( Parkinson, 2007 ), or for imaging plates over time ( Parkinson, 2007 ; Cobo et al, 2018 ; Reding et al, 2019 ). The specialization of these apparatuses increases the cost of construction as they include illuminators that provide transmitted light through the bottom of the plate ( Parkinson, 2007 ; Clarke et al, 2010 ; Brugger et al, 2012 ), climate control equipment ( Cobo et al, 2018 ; Reding et al, 2019 ), or fluorescence imaging capability ( Reding et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other apparatuses have been custom-made for automated colony counting ( Clarke et al, 2010 ; Brugger et al, 2012 ), imaging colonies in soft agar ( Parkinson, 2007 ), or for imaging plates over time ( Parkinson, 2007 ; Cobo et al, 2018 ; Reding et al, 2019 ). The specialization of these apparatuses increases the cost of construction as they include illuminators that provide transmitted light through the bottom of the plate ( Parkinson, 2007 ; Clarke et al, 2010 ; Brugger et al, 2012 ), climate control equipment ( Cobo et al, 2018 ; Reding et al, 2019 ), or fluorescence imaging capability ( Reding et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%